α-Amination of Phosphonates: A Direct Synthesis of α-Amino Phosphonic Acids and Their Derivatives - McDonald, Stacey L.; Wang, Qiu (Synlett, 2014)
A direct approach to access important α-amino phosphonic acids and their derivatives through the formation of C–N bonds is described. Several α-amination reactions of phosphonates that involve electrophilic aminating agents are reviewed. A recent development is highlighted in which an acyclic or cyclic amine is introduced into the α-position of a phosphonate in one step through deprotonative formation of an α-zincate followed by copper-catalyzed amination with an O-acylhydroxylamine.
Keywords: aminophosphonic acids; amination; phosphonates; copper catalysis; O-acylhydroxylamines; C–N bond formation